8 - L’Université de Ouagadougou : territoire de la contestation et de la répression des étudiants - Issa Sory (Journal of Higher Education in Africa, 2012)
The aim of this paper is to analyse the processes of territories’ formation and patterning which result from actors’ games, particularly between the local Section of Ouagadougou of the General Students Union of Burkina Faso (Union générale des étudiants burkinabé) and the University’s, municipal and state’s authorities. Since the early 1990’s, in the face the increasing number of students and the implementation of the Structural Adjustment Programmes, the setting of a Security Service and the relocation of Univer- sity accommodations have appeared as strategies intending to reduce the effects of students’ contestations. In 1998, « red sectors »–zones around defended institutions from demonstrations –are demarcated in the capital by the city’s authorities. The ability of a social movement in general, particular of student, to reach these sectors during periods of socio-political tensions is thus a marker of power balances between the Unions and the states authorities.